Learning the words AND knowing the concepts: an in‐depth study of one expert teacher's use of language as a cultural tool to support inquiry. (19th June 2019) - Hayden, Emily; Baird, Michelle Eades; Singh, Anupma
Abstract: This research explored the practices of one science teacher, expert in her field, as she worked to enact science discourse that incorporated language in naturalistic and rigorous ways. Difficulties in mastering the language of science contribute to troubling and persistent achievement gaps across demographic and gender groups. Science learning is based in discourse, with knowledge built by asking questions, exploring, revising views and asking new questions. But all too often students are not able to participate fully in these opportunities for discourse that is engaging and exploration due to the difficulty of science language. Qualitative analysis of this teacher's use of science discourse to establish clear links between essential science language and concepts and pre/post analysis of a science language assessment reveal important ways that teachers and researchers can work together to design and deliver instruction and assessment that supports students' mastery of sophisticated language and concepts. Results have implications for theory regarding science discourse; language learning, and conceptual development; and provide a model for teacher–researcher partnerships exploring important problems of teaching practice.